A Cognitive Architecture for the Coordination of Utterances - Gambi, Chiara; Pickering, Martin J. (Frontiers in Psychology, 2011)
Dialogue partners coordinate with each other to reach a common goal. The analogy with other joint activities has sparked interesting observations (e.g., about the norms governing turn taking) and has informed studies of linguistic alignment in dialogue. However, the parallels between language and action have not been fully explored, especially with regard to the mechanisms that support moment-by-moment coordination during language use in conversation. We review the literature on joint actions to show (i) what sorts of mechanisms allow coordination and (ii) which types of experimental paradigms can be informative of the nature of such mechanisms. Regarding (i), there is converging evidence that the actions of others can be represented in the same format as one’s own actions. Furthermore, the predicted actions of others are taken into account in the planning of one’s own actions. Similarly, we propose that interlocutors find it easy to coordinate their acts of production because they can represent their partner’s utterances, they can use these representations to build predictions, which are taken into account in the planning of self-generated utterances. Regarding (ii), we propose a new methodology to study interactive language that combines joint tasks with traditional psycholinguistic methods. In one class of paradigms, two participants are involved in simultaneous production and we manipulate the relationship between their utterances to investigate whether representations of other-generated utterances are built automatically. In a second class of paradigms, the production of an utterance is distributed between two speakers (i.e., they complete each other’s utterances). The timing of their contributions is varied; we are interested in the extent to which predictions about other-generated utterances are integrated in the planning of one’s own utterances. Finally, we argue that our account of joint language use leads to a new view on isolated comprehension.